(untitled) (Research, Society and Development, 2021)
The population increase in urban centers represents a great challenge, as the population increases, more areas will be deforested for housing construction, more materials and consumer goods are generated to meet the population’s needs. The activities that men carry out result in residues that are mostly inappropriately released, compromising the environment. The release of these residues and the non-treatment of them contribute to the degradation of the biosphere, impairing the quality of life on the planet and enabling the proliferation of diseases for the population. The poor management of urban solid waste has forced Brazilian municipalities to find alternatives for this management and final disposal of these materials. This research exposes the current situation of MSW in the municipality of Floresta - PE. The results obtained show that the treatment and final disposal of solid waste in the city is inadequate, generating environmental and social impacts for the population. The data obtained in this research will serve to support the construction of a solid waste management plan and environmental education in the municipality with collective actions to be developed with the population.